Probiotic pre-treatment reduces gliclazide permeation (ex vivo) in healthy rats but increases it in diabetic rats to the level seen in untreated healthy rats - Al-Salami, Hani; Butt, G.; Tucker, I.; Skrbic, R.; Golocorbin-Kon, S.; Mikov, M. (2008)
Aim. To investigate the influence of probiotic pre-treatment on the permeation of the antidiabetic drug gliclazide in healthy and diabetic rats. Methods. Wistar rats (age 2-3 months, weight 350 ± 50 g) were randomly allocated into one of 4 groups (N = 16 each group): healthy control, healthy probiotic, diabetic control, and diabetic probiotic. Probiotics (75 mg/kg, equal quantities of Lactobacillus acidophilus, Bifidobacterium lactis, and Lactobacillus rhamnosus) were administered twice a day for three days to the appropriate groups after diabetes had been induced with alloxan i.v. 30 mg/kg. Rats were sacrificed, ileal tissues mounted in Ussing chambers and gliclazide (200 µg/mL) was administered for the measurement of the mucosal to serosal absorption Jss(MtoS) and serosal to mucosal secretion Jss(StoM) of gliclazide. Results. Treatment of healthy rats with probiotics reduced Jss(MtoS) of gliclazide from 1.2 ± 0.3 to 0.3 ± 0.1 µg/min/cm2 (P < 0.01) and increased Jss(StoM) from 0.6 ± 0.1 to 1.4 ± 0.3 (P < 0.01) resulting in net secretion while, in diabetic tissues, treatment with probiotics increased both Jss(MtoS) and Jss(StoM) fluxes of gliclazide to the comparable levels of healthy tissues resulting in net absorption. Discussion. In healthy rats, the reduction in Jss (MtoS) after probiotics administration could be explained by the production of bacterial metabolites that upregulate the mucosal efflux drug transporters Mrp2 that control gliclazide transport. In diabetic rats, the restored fluxes of gliclazide after probiotic treatment, suggests the normalization of the functionality of the drug transporters resulting in a net absorption. Conclusion. Probiotics may alter gliclazide transport across rat ileal tissue studied ex vivo. © 2008, Archives of Drug Information.